2020
DOI: 10.23887/jere.v4i3.27450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physics Education Technology (PhET) Simulations: Evidence from STEM Students’ Performance

Abstract: This study aimed to find out if Physics Education Technology (PhET) simulations can improve the performance of the Baybay City Senior High School STEM students on the selected topic in physics, that is, electrodynamics. This study utilized a quasi-experimental type where pre-test and post-test are multiple choice type of test and involved 72 STEM students. The grouping of the students was identified based on their sections, one section served as the control group and other is the experimental group. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
4
17
0
4
Order By: Relevance
“…This quantitative research utilized a quasi-experimental design based on the current study, involving two equivalent independent groups engaged in pretest-posttest (Suarez & Casinillo, 2020;Yunzal & Casinillo, 2020). Some descriptive statistics was used to describe the data collected and in determining the significant difference or the effectiveness of the intervention, T-test was used as inferential statistics method.…”
Section: Methodsmentioning
confidence: 99%
“…This quantitative research utilized a quasi-experimental design based on the current study, involving two equivalent independent groups engaged in pretest-posttest (Suarez & Casinillo, 2020;Yunzal & Casinillo, 2020). Some descriptive statistics was used to describe the data collected and in determining the significant difference or the effectiveness of the intervention, T-test was used as inferential statistics method.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, students expressed positive views of the approach (e.g., students expressed that physics is fun and easy). However, Yunzal, Jr. & Casinillo, (2020), found that teaching electrodynamics using PhET simulations did not significantly improve students" learning, although students showed interest in playing with the simulations. A study that seems closer to the current study is the one conducted by Astutik & Prahani, (2018) who engaged junior high school students in collaborative groups using PhET simulations and assessed students" scientific creativity after going through a natural science lesson.…”
Section: Related Literaturementioning
confidence: 95%
“…Penelitian tentang penggunaan PHET simulation di dalam pembelajaran fisika telah banyak dilakukan. Seperti penelitian yang telah dilakukan oleh Yunzal & Casinillo (2020) bahwa pembelajaran fisika dengan menggunakan PHET simulation lebih menarik minat dan perhatian mahasiswa. Selain itu, ada perbedaan kinerja (performance) mahasiswa sebelum dan sesudah menggunakan PHET simulation.…”
Section: Pendahuluanunclassified